EXPLORING THE POTENTIALS OF CEREAL FOOD WASTE IN ANAEROBIC DIGESTION - Salim, A. A.; Zubairu, S. M.; Isma’il, M.; Ahmed, A.; Hassan, A. W.; Abdulkadir, J.; Ityonum, B. I. (FUDMA JOURNAL OF SCIENCES, 2024)
Cereal food waste makes up a significant part of municipal solid waste, and its proper treatment has become an urgent issue due to its increasing generation. In Nigeria, where around 50% of municipal waste is organic, this study focuses on the need for effective waste management. It highlights the negative environmental and economic impacts of improper disposal methods. The study examines the potential of using cereal food waste in anaerobic digestion for biogas production. Cereal food waste was collected from student hostels at the College of Nursing and Midwifery Malumfashi, sorted, and converted into a composite for anaerobic digestion. An anaerobic digester was constructed using a 25-litre plastic container designed for batch loading. The anaerobic digestion process was carried out for 30 days. The results show that a total biogas volume of 14,634 mL was produced during this time. The daily biogas yields varied, reaching its highest point on the 5th day. This finding underscores the importance of addressing food waste in the cereal supply chain to ensure sustainable food production and consumption. The results demonstrate that cereal food waste has significant potential for biogas production, which can contribute to sustainable waste management and help address environmental challenges linked to food waste. Based on these findings, the study recommends promoting the use of biogas technology to improve food waste management, thus enhancing environmental sustainability and supporting economic development.